Interaction design content and method : a case study on industrial design students / Mohammad Zaki Sharifuddin - Sharifuddin, Mohammad Zaki (2005)
Due to the borderless communications in the Information world today, a shift of focus is seen occurring from "product-as-object" approach towards the notion of "product-as-event" where dynamic functionality and behavioral qualities of the new products are increasingly important. Because of the interactive nature of these products, the trend has enhanced the importance of Information Ergonomics in general and Interaction Design in particular. However, the education of computer professionals often concentrates on the understanding of computational mechanisms, and on engineering methods to ensure that the mechanisms behave according to the intention of the programmer. This research looks at the current product design issues involving the single-sided focus on the design of interactive products and highlights the importance of Industrial Design. As a conceptual framework, this research study includes reviews on previous research relevant to the scope of 'design' in relation to Industrial Design, which involve the design process, design drawings and design methods. A case study, involving qualitative and quantitative method was used in this research. A classroom of Industrial Design students doing Applied Industrial Design subject at Universiti Teknologi MARA, Shah Alam, was taken as the study in understanding the thinking process involved in delivering content for interactive products. Seven students were selected for the study and their design documents such as; sketches, drawings diagrams and reports were analyzed using three stages of analyses. Various Interaction Design concern were discussed and towards the end of the study a design method was proposed. This research documented a specific type of project for the design of 'Cleaning Appliances' where design intention and creative ability of the students in delivering Interaction Design content and method was sought. Although without proper guidelines from the Interaction Design discipline, the students showed the ability in delivering basic interactive product design concepts using the Industrial Design knowledge. This research study contributes to the knowledge of design disciplinary areas in both Human Computer Interaction and Industrial Design, which highlights the important role of Industrial Design students in delivering Interaction Design content and methods. 11 COPYRIGHT